PERAN SOSIAL PEREMPUAN DAYAK DI TIGA CERITA PENDEK KORRIE LAYUN RAMPAN - Aquari Mustikawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2018)
This study describes the social role of Dayak women, both in the domestic and public spaces in three Korrie Layun Rampan short stories, namely "Perlawanan", "Riam" and "Upacara tak Selesai". The role of women includes the ways women maintain their life and customary land as the important thing in their society. The focus problem of this research is what are the roles of Dayak women in the domestic and public spaces. To solve problems and achieve goals, qualitative descriptive methods are used, by describing the role of Dayak women in their lives and their resistance to gender injustice. Feminist theory is used to analyze the forms and roles of Dayak women in overcoming their problems. The results of the study prove/show that Dayak women are socially and intellectually independent women. This study concludes that Dayak women have a very important role in their community because they have social and intellectual independence.